Human embryos and preimplantation genetic technologies : ethical, social, and public policy aspects - Sills, E. Scott; Palermo, Gianpiero D. (Academic Press, 2019)
Human Embryos and Preimplantation Genetic Technologies: Ethical, Social, and Public Policy Aspects presents the first holistic analysis of PGD and PGS as it is practiced and regulated worldwide. In addition to scientific and technical aspects, the book provides perspectives on the ethical, legal, religious, policy and social implications of global assisted reproduction technologies, including in Africa, Asia, Europe, North and South America, and Australia. Chapters cover history, ethics, feminism, family dynamics, psychological and interpersonal factors, the current state of PGD and PGS in 20 different sovereign nations and religious communities, and provide an analysis of public policy concerns and future directions.